Terapia fotodinâmica com fotossensibilizadores fenotiazínicos: mecanismos de morte celular - Gonçalves, José Marcelo Lacerda Alves (2019)
Photodynamic therapy is a promising treatment option that can be used in several areas of health. The technique is based on the combination of a photosensitizing agent and light. The photosensitizer after exposure to visible radiation, generates reactive oxygen species that lead to cell death. Phenothiazinium dyes are a class of molecules that have properties suitable for Photodynamic Therapy, with only Methylene Blue and Toluidine Blue being extensively studied. Recently other phenothiazinium dyes, such as Azure A and Azure B, have started to be studied and it has been reported that their efficacy is dependent on aggregation. In this context, it is not yet known whether aggregation influences the mechanism of photoinduced cell death. The objective of this work was to evaluate the mechanisms of cell death induced by photodynamic therapy with the photosensitizers Azure A, Azure B and Methylene Blue, relating to the production data of reactive oxygen species. Tests were performed to quantify the production of reactive oxygen and nitrogen species, and evaluation of mechanisms of cell death using the IC50 concentrations of photosensitizers, at different times after exposure to light. The results showed that Methylene Blue was the photosensitizer that presented the highest production of reactive species (oxygen and nitrogen), followed by Azure B, whereas the production of these species photoinduced by Azure A is very low, with no difference in relation to the control group. Methylene blue is the most effective in causing cell death among the compounds tested and the photosensitizer that causes greater loss of mitochondrial membrane potential. All SFs lead to some labeling with propidium iodide 3h after irradiation, but only AA continues to present high PI + marking at 24 and 48h after treatment. Other assays are still needed to clarify the mechanisms of photodamaged cell death after photodynamic Therapy, but there are indications that Azure A causes necrosis to a greater extent due to loss of cell membrane integrity at different times after treatment, whereas Methylene Blue and Azure B would cause necrosis to some extent, but apoptosis would be the mechanism most involved.